Mucocele operowana nożem elektrycznym – opis przypadku = Mucocele removed by electric knife – case report - Ratajek-Gruda, Monika; Szczepkowska, Aleksandra; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2016)
Ratajek-Gruda Monika, Szczepkowska Aleksandra, Osica Piotr, Janas-Naze Anna. Mucocele operowana nożem elektrycznym – opis przypadku = Mucocele removed by electric knife – case report. Journal of Education, Health and Sport. 2016;6(6):629-636. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56769 http://ojs.ukw.edu.pl/index.php/johs/article/view/3642 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Mucocele operowana nożem elektrycznym – opis przypadku Mucocele removed by electric knife – case report Monika Ratajek-Gruda, Aleksandra Szczepkowska, Piotr Osica, Anna Janas-Naze Zakład Chirurgii Stomatologicznej, Uniwersytet Medyczny w Łodzi dr n. med. Monika Ratajek-Gruda, lek. dent. Aleksandra Szczepkowska, dr n. med. Piotr Osica, dr hab. n. med. prof. nadzw. Anna Janas-Naze Zakład Chirurgii Stomatologicznej Uniwersytet Medyczny w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze ul. Pomorska 251 92-213 Łódź email: mogruda@wp.pl Praca finansowana przez UM w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001. Streszczenie Mucocele jest najczęstszą chorobą małych gruczołów ślinowych. Jej leczenie jest chirurgiczne i może być wykonane metodą tradycyjną z użyciem skalpela, nożem elektrycznym lub laserem. W pracy przedstawiono przypadek 30. letniej pacjentki, u której usunięto torbiel zastoinową nożem elektrycznym. Uzyskano dobry efekt terapeutyczny i kosmetyczny. Hasła indeksowe: mucocele, torbiel zastoinowa, nóż elektryczny, jama ustna. Summary Mucocele is the most common disease of the small salivary glands. The treatment of such lesion is always surgical and can be either traditional – with the use of a scalpel or modern, using the electric knife or laser. The article presents a case of 30 y. o. patient, who underwent surgical removal of the mucocele with the use of an electric knife. Positive therapeutic and cosmetics effect was obtained. Key words: mucocele, congestive cyst, electric knife, oral cavity.